The relaxation phenomena in irradiated PZT type piezoceramics - Zachariasz, R.; Ilczuk, J.; Brus, B. (Functional Materials, 2007)
The samples of PZT type multi-component piezoceramics Pb₀.₉₇₅Ba₀.₀₁Ca₀.₀₁Sr₀.₀₀₅(Zr₀.₅₂Ti₀.₄₈)O₃ + 1.4 wt.% Bi₂O₃ + 0.3 wt% GeO obtained by hot pressing were shaped as (30x10x0.9) mm3 plane-parallel plates. Some samples were subjected to polarization by low temperature method (T = 423 K, Ep = 30 kV/cm, t = 30 min), and others were γ-irradiated (200 kGy, ⁶⁰Co). For all specimens, temperature dependences of the internal friction Q⁻¹ and Young's modulus E were determined while heating at a rate of 3 K/min. The Q⁻¹(T) curve shows two peaks PR and PT,' located for non-irradiated sample at TR= 380 K, TF = 640 K, respectively. For samples irradiated at 200 kGy dose, the PR peak shifts towards higher temperatures, while PT,' towards lower ones. The values of Young's modulus E are decreased in the area of the PR and PF peaks. At room temperature, the E value is 133 GPa for the non-irradiated sample and 150 GPa for the irradiated one. The relaxation peak PR has been shown to be due to the domain boundary interaction with oxygen vacancies while the PF one is related to the phase transition at the Curie point.